2003
DOI: 10.1128/jvi.77.18.9969-9978.2003
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Using Rotaviruses Bind α2β1 Integrin α2 I Domain via VP4 DGE Sequence and Recognize αXβ2 and αVβ3 by Using VP7 during Cell Entry

Abstract: Integrins ␣2␤1, ␣X␤2, and ␣V␤3 have been implicated in rotavirus cell attachment and entry. The virus spike protein VP4 contains the ␣2␤1 ligand sequence DGE at amino acid positions 308 to 310, and the outer capsid protein VP7 contains the ␣X␤2 ligand sequence GPR. To determine the viral proteins and sequences involved and to define the roles of ␣2␤1, ␣X␤2, and ␣V␤3, we analyzed the ability of rotaviruses and their reassortants to use these integrins for cell binding and infection and the effect of peptides DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
187
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(204 citation statements)
references
References 54 publications
12
187
0
5
Order By: Relevance
“…The peptide sequence arginine-glycine-aspartic acid (RGD) is the laminin-binding domain to the ␣ 2␤1-integrin (28). The peptide sequence glycine-proline-arginine (GPR) is the fibrinogen-binding domain to the ␣ v␤3-integrin (13). The peptide sequence GHRP served as a negative control.…”
Section: Viral Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide sequence arginine-glycine-aspartic acid (RGD) is the laminin-binding domain to the ␣ 2␤1-integrin (28). The peptide sequence glycine-proline-arginine (GPR) is the fibrinogen-binding domain to the ␣ v␤3-integrin (13). The peptide sequence GHRP served as a negative control.…”
Section: Viral Assaysmentioning
confidence: 99%
“…Consistent with the in vivo findings, RRV was better able to replicate in cholangiocytes than hepatocytes. Because the ability of rotavirus to infect cells appears to be regulated by cell-surface expression of the integrins ␣ 2 ␤ 1 , ␣ 4 ␤ 1 , ␣ v ␤ 3 , and ␣ x ␤ 2 , which serve as viral receptors (8,13,14,16,21), the cholangiocyte was surveyed for integrin expression and found to uniquely express the ␣ 2 ␤ 1 -integrin when compared with hepatocytes. Based on this information, we hypothesized that expression of the ␣ 2 ␤ 1 -integrin serves as a determinant governing cholangiocyte susceptibility to RRV infection contributing to the mechanism by which rotavirus initiates the experimental model of biliary atresia.…”
mentioning
confidence: 99%
“…Similarly, the uptake of adenovirus type 3 (Ad3) was recently shown to be dependent on the αV integrin and on Rac1-and Pak-1-dependent actin remodelling (Amstutz et al, 2008). Finally, α2β1, αXβ2, α4β1 and α4β7 integrins promote the entry of rotaviruses (Coulson et al, 1997;Graham et al, 2005;Graham et al, 2003;Graham et al, 2006;Guerrero et al, 2000;Hewish et al, 2000), although it remains to be seen whether this follows a phagocyticlike process.Overall, several viral and bacterial pathogens use integrin signalling to enter host cells in an actin-dependent process. Deciphering the molecular pathways that are used for local, transient, integrin-triggered actin and membrane remodelling should aid in the design of drugs that will help fight infection in vitro and in vivo.…”
mentioning
confidence: 99%
“…The RV3-BB vaccine is derived from a neonatal rotavirus strain which binds to specific receptors in the newborn gut and is integrin independent and, may inherently offer protection from maternal antibodies. 34 In this study, high levels of IgA in colostrum or breast milk did not appear to inhibit the serum IgA response or stool excretion following 3 doses of RV3-BB rotavirus vaccine in either a neonatal schedule with the first dose at age 0-5 d or an infant schedule with the first dose at 8 weeks of age. These findings are consistent with studies from North India 25 and South Africa 26 which found little difference in anti-rotavirus IgA seroconversion irrespective of whether breastfeeding was withheld for either 30 minutes or one hour before and after RV1 vaccine administration.…”
Section: Discussionmentioning
confidence: 92%
“…However, a potential advantage of a vaccine based on a human neonatal rotavirus strain delivered at birth is the proposed intrinsic structural characteristics that enable it to avoid neutralisation by maternal and breast milk antibodies. 34 Data from the placebo group provided a negative control for the rate of natural rotavirus infection in this study population. Interestingly one of the participants in the placebo group was excreting RV3-BB rotavirus vaccine in the stool at both 20 weeks and 28 weeks, which suggested presence of this strain in the community.…”
Section: Discussionmentioning
confidence: 99%